Разложить на множителиc²+4вс+4в²6x²y²-24x²z²2a-2b+ca-cb9x²-(x-1)²-3x(x+3)+x³+27

Разложить на множители c²+4вс+4в² 6x²y²-24x²z² 2a-2b+ca-cb 9x²-(x-1)² -3x(x+3)+x³+27
Гость
Ответ(ы) на вопрос:
Гость
... = (с+2в)^2  ... = 6x^2*(y^2 - 4z^2) = 6x^2*(y-2z)(y+2z)  ... = 2(a-b) + c(a-b) = (2+c)(a-b)  ... = (3x - (x-1))(3x + (x-1)) = (2x+1)(4x-1)  ...
Гость
                                     Решение: Разложить на множители c²+4вс+4в²=(c+2b)*(c+2b) 6x²y²-24x²z²=6x^2(y^2-4z^2)=6x^2*(y-2z)(y+2z) 2a-2b+ca-cb=2(a-b)+x(a-b)=(a-b)(2+x) 9x²-(x-1)²=(3x+x-1)(3x-x+1)=(4x-1)(2x+1) -3x(x+3)+x³+27=-3x(x+3)+(x+3)(x^2+9-3x)=(x+3)(x^2+9-3x-3x)=(x+3)(x-3)^2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы